2019
DOI: 10.1177/0267659119878006
|View full text |Cite
|
Sign up to set email alerts
|

Custodiol cardioplegia solution compared to cold blood cardioplegia in pediatric cardiac surgery: a single-institution experience

Abstract: Objective: Custodiol is an intracellular, crystalloid cardioplegia solution that is a single-dose alternative to multi-dose cold blood cardioplegia; however, there is scarce data regarding its use in infants and children. The objective of this study was to compare its impact on myocardial function in infants. Methods: Single-center retrospective review including 132 patients <12 months old undergoing biventricular repair. There were 106 patients who received single-dose Custodiol and 27 patients who receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…A single-dose HTK perfusion regimen is becoming more frequent in technically complex heart surgeries requiring a long AC. The median AC time in this study cohort was above 80 min, which is consistent with previous studies where AC time exceeded 60 min [5,14] . This retrospective study aimed to investigate the clinical influence of high dosage HTK perfusion on neonatal patients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A single-dose HTK perfusion regimen is becoming more frequent in technically complex heart surgeries requiring a long AC. The median AC time in this study cohort was above 80 min, which is consistent with previous studies where AC time exceeded 60 min [5,14] . This retrospective study aimed to investigate the clinical influence of high dosage HTK perfusion on neonatal patients.…”
Section: Discussionsupporting
confidence: 88%
“…The median AC time in this study cohort was above 80 min, which is consistent with previous studies where AC time exceeded 60 min. [ 5 , 14 ] This retrospective study aimed to investigate the clinical influence of high dosage HTK perfusion on neonatal patients. The HTK dosage in the high-dose group was significantly higher than in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…As regards inotropic support in this study, maximum VIS was lower in the HHB group, after 24 h and 48 h (p=0.133 and 0.453, respectively). However, there was no statistically significant difference between both groups Bibevski et al (Bibevski et al 2020) proved that there was a significantly lower inotrope score in the custodiol (9.3 ± 2.6) in comparison with the blood group (10.4 + 3), p= 0.03. In their study, scores were calculated for all patients within the first 48 h after surgery, and the highest calculated score was recorded.…”
Section: Discussionmentioning
confidence: 91%
“…Also, Bibevski et al (Bibevski et al 2020) found that there was no difference as regards biventricular function assessed using echocardiography (LVEF, LVFS, RVFAC) between cold blood microplegia (blood with K+ at 30 mEq and magnesium 10 mL/L) and HTK crystalloid solution group.…”
Section: Discussionmentioning
confidence: 99%
“…Custodiol is an intracellular, crystalloid cardioplegia solution that is given in a single dose that lasts for 3 h [ 8 ]. The use of Custodiol in pediatric cardiac surgery is not popular, and there is a paucity of studies comparing Custodiol vs. blood cardioplegia in pediatric patients [ 9 ]. Currently, the efficacy and safety of Custodiol over blood cardioplegia in pediatric cardiac surgery have not been proven.…”
Section: Introductionmentioning
confidence: 99%